THE CONTRIBUTION OF ADAM SMITH TO THE DEVELOPMENT OF THE CONCEPT OF EQUILIBRIUM IN ECONOMICS (Third Sector Social Economic Review, 2018)
In this study, Adam Smith’s contributions to the concept of equilibrium were examined. ‘Equilibrium’, which is the essential analysis tool for literature and education of the mainstream economics, represents an optimal and ideal state such as in natural sciences. Although ‘equilibrium’ stood out as one of the main concepts in the birth of mainstream economics, it had not yet had a central statue for the age of Smith. However, it is possible to trace the concept of equilibrium in the studies of Smith who is known as the founder of economics. The aim of this study is to reveal these traces of the concept of equilibrium and to evaluate the contributions made by Smith for the development path of the concept in economic analysis.
Keywords: Adam Smith; Equilibrium; Price Mechanism; Natural Price; Invisible Hand